Zohreh Khosrobeigi, Maria Koutsombogera, Carl Vogel - Vogel, Carl; Khosrobeigi, Zohreh; Koutsombogera, Maria (My University, 2023)
This paper studies the relationship between conversational features related to gesture, conversational dominance, collaboration, and personality traits. Specifically, we examine the interaction of motion energy and factors associated with dialogues and participants therein. We observe among semiotic types of gesture in dialogue higher motion energy in Beats, Deictics and Iconics than Symbolics, but lower in Beats than arbitrary hand movements. Dominance and collaboration are correlated with motion energy when contentful semiotic gesture types are excluded. Different collaboration scores present different associations on the level of motion energy. The findings quantify the extent to which the motion energy of participants contributes to judgments of dominance and collaboration in dialogue.
2023 International Conference on Multimedia Computing, Networking and Applications (MCNA)
PUBLISHED
Valencia, Spain
Keywords: Motion Energy; Interaction; Collaboration; Gesture; Dominance; Creative Technologies; Digital Engagement; Digital Humanities; Telecommunications; ARTIFICIAL INTELLIGENCE; Computational Linguistics; gesture